2007
DOI: 10.3141/1998-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Simple Performance Test |E*| of Accelerated Loading Facility Mixtures and Prediction |E*|

Abstract: The dynamic modulus, |E*|, of asphalt mixture has recently drawn much attention in the asphalt community. The |E*| test has been suggested by NCHRP Projects 9-19 and 9-29 as the simple performance test (SPT) to verify the performance characteristics of Superpave® mixture design. In addition, it has been recommended as the potential quality control-quality assurance parameter in the field. The dynamic modulus, |E*|, is an input to the Mechanistic-Empirical Pavement Design Guide (M-E PDG) and also supports the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…There are several observations in the literature that the various models lose accuracy at the low and/or high temperature extremes (Pellinen, 2001;Schwartz 2005;Dongre et al 2005;Bari and Witczak 2006;Al-Khateeb et al 2006;Azari et al 2007). Table 1 summarizes the average prediction errors for all of the models stratified by temperature.…”
Section: Fig 3 Overall Bias In Model Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several observations in the literature that the various models lose accuracy at the low and/or high temperature extremes (Pellinen, 2001;Schwartz 2005;Dongre et al 2005;Bari and Witczak 2006;Al-Khateeb et al 2006;Azari et al 2007). Table 1 summarizes the average prediction errors for all of the models stratified by temperature.…”
Section: Fig 3 Overall Bias In Model Predictionsmentioning
confidence: 99%
“…Several studies have indicated that the Witczak |E*| models show significant scatter especially at the low and/or high |E*| modulus extremes (Pellinen, 2001;Schwartz 2005;Dongre et al 2005;Bari and Witczak 2006;Al-Khateeb et al 2006;Azari et al 2007). There are also suggestions that the Witczak |E*| predictive models are dominated by the influence of temperature and understate the influence of other mixture parameters (Schwartz 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted by Al-Khateeb et al [14] and Yousefdoost et al [15] showed that the NCHRP 1-37A model produced more accurate E* predictions compared to the NCHRP 1-40D model, particularly at the higher temperature range [. Whereas a recent [19] concluded that Hirsh and NCHRP 1-37A models generated more accurate E* values compared to the NCHRP 1-40D model based on 1032 E* measurements from 25 mixes from the state of Idaho.…”
Section: Comparison Studies Of Witczak and Hirsh Modelsmentioning
confidence: 99%
“…Several studies focused on using laboratory measured E* data to compare and evaluate the accuracy of the two well-known Witczak models which are the NCHRP 1-37A and NCHRP 1-40D [14][15][16]. The studies conducted by Al-Khateeb et al [14] and Yousefdoost et al [15] showed that the NCHRP 1-37A model produced more accurate E* predictions compared to the NCHRP 1-40D model, particularly at the higher temperature range [.…”
Section: Comparison Studies Of Witczak and Hirsh Modelsmentioning
confidence: 99%
“…For example, at Level 1, the asphalt binder and the HMA are tested in the laboratory to measure dynamic modulus. However, the measurement of dynamic modulus in the laboratory is not always feasible because of the tedious experiments and it may also take several days to develop a single master curve [6]- [8].…”
Section: Introductionmentioning
confidence: 99%